Phytocoetes sinensis n. sp. and Telmatactis clavata (Stimpson, 1855), two poorly known species of Metridioidea (Cnidaria: Anthozoa: Actiniaria) from Chinese waters - Li, Yang; Liu, Rui-Yu; Xu, Kuidong (Zootaxa, 2013)
Two acontiate sea anemones, Phytocoetes sinensis n. sp. within the family Halcampactinidae and Telmatactis clavata (Stimpson, 1855) within the family Andvakiidae, are described from the coastal region of Chinese waters. Phytocoetes sinensis is an elongated sea anemone discovered from the intertidal mudflat in the East China Sea. The new species is very similar to its only congener P. gangeticus, but differs distinctly by the larger body size (length usually 61–130 mm vs. no more than 30 mm) and a higher number of mesenteries (48 pairs vs. 12 or probably 24 pairs) and tentacles (usually 72–118 vs. 50–65). This is the first record of Halcampactinidae in China. Telmatactis clavata has been reported only from the warm waters of Japan. We redescribed the species in more details based on specimens collected from the South China Sea. So far the species is known only from warm waters in the western Pacific.